Liability claim for damages caused by delay in completing a public project - Che Amnah Jusoh; Asmawan Mohd Sarman (Eyup Artvinli, Institute of Education in Eskisehir Osmangazi University, 2021)
Every year, more people file lawsuits seeking compensation for their losses and costs as a result of the delay in getting their claims processed. Most of the time, the issue arises because the contractor does not understand the provision that permits claiming losses and costs as a result of an extension of time. The contractor will attempt to compensate for the delay if an extension of time was granted for an excused cause. However, extra compensable is not applicable to all excused reasons. As a result, the Contractor fails to make a claim for E.O.T. that is in accordance with the contract's specifications. Lack of timely submission of an intent-to-claim notification is the most common cause of Contractor failure in P.W.D. project claims for loss and cost. submitting claims without supporting documentation or proof after the Contractor has failed to claim loss and cost in P.W.D. projects within the specified timeframe PWD Form 203/203A (Rev.1/2010) and PWD Form D.B. (50.2 PWD Form D.B., Rev.1/2010) require the Contractor to provide proof of the specifics of his claim for verification by S.O. The Contractor will have three (3) months from the date of practical completion to provide the necessary proof. So this research is critical to interpreting clauses that could justify a claim for loss and expense due to a time extension, as well as to examine the process and procedure involved in evaluating claims for loss and expense as well as to appraise clauses and claims that are permitted for loss and expense due to a time extension under government projects.